IDENTIFYING COPING MECHANISMS TO OVERCOME SLEEP DISTURBANCE AMONG THE ELDERLY - Divanee Chandrasegar; Siti Nordarma Ab Rahman; Nor Shafrin Ahmad, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Sleep disturbances are a prevalent issue among the elderly, significantly affecting their quality of life, cognitive function, and physical health. This study utilized the Nominal Group Technique (NGT) to identify and rank effective coping strategies for managing sleep disturbances. Structured discussions were conducted with a panel of experts and elderly individuals who had experienced sleep disturbances. The findings highlighted that physical comfort and environmental adjustments were the most effective strategies. The use of supportive pillows and mattresses (95.24%) and avoiding excessive water intake before bed (95.24%) ranked as top priorities. Other highly rated strategies included reducing light exposure (90.48%), maintaining a cosy sleeping environment (80.95%), and relaxation techniques such as aromatherapy (85.71%). While behavioural changes such as mindfulness meditation (71.43%) and avoiding caffeine before bed (71.43%) were recognized as beneficial, they were ranked lower due to challenges in adherence. The study underscores the importance of a multifaceted approach integrating lifestyle, psychological, and physical interventions to improve sleep quality. The study provides evidence-based recommendations for policymakers, healthcare professionals, and caregivers to develop personalized sleep intervention plans for older adults. Future research should explore digital health interventions, long-term effectiveness, and policy-driven solutions to further enhance sleep management among the elderly.